2019
DOI: 10.1177/2055207619882181
|View full text |Cite
|
Sign up to set email alerts
|

Use of mobile health applications for health-promoting behavior among individuals with chronic medical conditions

Abstract: Background: Chronic medical conditions (CCs) are leading causes of morbidity and mortality in the United States. Strategies to control CCs include targeting unhealthy behaviors, often through the use of patient empowerment tools, such as mobile health (mHealth) technology. However, no conclusive evidence exists that mHealth applications (apps) are effective among individuals with CCs for chronic disease self-management. Methods: We used data from the Health Information National Trends Survey (HINTS 5, Cycle 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 37 publications
7
60
0
1
Order By: Relevance
“…Notably, the more contemporary term digital health includes categories such as mHealth, health information technology, wearable devices, telehealth and telemedicine, and personalized medicine [ 20 ]. Our findings complement prior studies exploring various aspects of mHealth and eHealth to support patients’ behavior change and self-management across health conditions—often done via telemedicine, SMS text messaging, or smartphone apps [ 21 - 26 ]—as well as studies showing that tablets and smartphones can help support chronic disease management [ 18 ]. Novel uses of mobile devices are being explored to support shared decision via digital phenotyping [ 27 ] or “moment-by-moment quantification of the individual-level human phenotype in-situ using data from smartphones and other personal digital devices” [ 28 ].…”
Section: Discussionsupporting
confidence: 82%
“…Notably, the more contemporary term digital health includes categories such as mHealth, health information technology, wearable devices, telehealth and telemedicine, and personalized medicine [ 20 ]. Our findings complement prior studies exploring various aspects of mHealth and eHealth to support patients’ behavior change and self-management across health conditions—often done via telemedicine, SMS text messaging, or smartphone apps [ 21 - 26 ]—as well as studies showing that tablets and smartphones can help support chronic disease management [ 18 ]. Novel uses of mobile devices are being explored to support shared decision via digital phenotyping [ 27 ] or “moment-by-moment quantification of the individual-level human phenotype in-situ using data from smartphones and other personal digital devices” [ 28 ].…”
Section: Discussionsupporting
confidence: 82%
“…Considering previous nursing intervention studies [ 60 , 61 , 62 ], patients’ continuous disease management would require combined interventions including web-based or mobile-based interventions, not just face-to-face nursing education and nursing interventions. Electronic health (eHealth) or mobile health (mHealth) interventions can induce positive behavior changes and promote healthy lifestyles [ 63 ], allowing easy access. Moreover, effective nursing strategies including medication education, post-discharge programs, and nurse provider healthcare services for CVD patients are necessary to increase health-promoting behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Roshanov et al [36] argued that this probably is due to the increased empowerment of the patients when they become actively involved in their care. Mahmood et al [37] found that patients using mHealth applications to track progress on a health-related goal performed health-related decisions and engaged in health-related discussions with the healthcare providers to a larger extent than patients not using such mHealth applications.…”
Section: Patient Empowermentmentioning
confidence: 99%